Novel particle sizing techniques - Chen, Rui (2013)
Two novel approaches to particle size measurement are investigated; these are designated as Particle Movement Displacement Distribution (PMDD) method and Separated Multiple Image Technique (SMIT). An advantage of these methods compared with the established particle sizing methods of Static Light Scattering (SLS) and Dynamic Light Scattering (DLS) is that PMDD and SMIT do not suffer from the intensity weighting problem that affects SLS and DLS.